2018
DOI: 10.2147/cmar.s174745
|View full text |Cite
|
Sign up to set email alerts
|

ZNF259 promotes breast cancer cells invasion and migration via ERK/GSK3β/snail signaling

Abstract: PurposeZinc finger protein 259 (ZNF259), also known as ZPR1, is a zinc finger-containing protein that can bind the intracellular tyrosine kinase domain of EGFR. At present, our knowledge on ZNF259 in cancers is limited. Here, we aimed to explore the biological functions of ZNF259 in breast cancer and reveal their mechanisms.Patients and methodsThe expression of ZNF259 was measured in 133 cases of breast cancer by immunohistochemistry. The online database Kaplan–Meier (KM) Plotter Online Tool was used to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The ERK pathway comprises several proteins that belongs to the family of mitogen-activated protein kinases (MAPK). These regulate diverse physiological and cellular processes, such as gene expression, cell division, survival, apoptosis, differentiation, and motility [15,16]. In metastatic processes, the MAPKs regulate EMT, invasion, angiogenesis, and resistance to therapy [7].…”
Section: Extracellular-signal Regulated Kinase: Structure and Funcmentioning
confidence: 99%
See 1 more Smart Citation
“…The ERK pathway comprises several proteins that belongs to the family of mitogen-activated protein kinases (MAPK). These regulate diverse physiological and cellular processes, such as gene expression, cell division, survival, apoptosis, differentiation, and motility [15,16]. In metastatic processes, the MAPKs regulate EMT, invasion, angiogenesis, and resistance to therapy [7].…”
Section: Extracellular-signal Regulated Kinase: Structure and Funcmentioning
confidence: 99%
“…This leads to an increase in the expression of ZO-1, claudin, and occludin and adequate formation of adherent junctions [177]. Likewise, the expression of ZNF259 (Zinc finger protein 259) in MCF-7 and MDA-MB-231 cell lines increases the phosphorylation of MEK, ERK, and GSK3β and expression of Snail, while diminishing the ERK-dependent expression of EMT markers [16]. On the other hand, in the T47D and MDA-MB-231 cell lines, a positive feedback was observed between the EMT transcription factor Snail and p-ERK, which favors the expression and nuclear localization of both proteins [178].…”
Section: Relationship Between Erk and Epithelial–mesenchymal Transmentioning
confidence: 99%
“…A previous study showed that ERK inhibitor U0126 could inhibit the levels of p-ERK and Snail and then restore E-cadherin expression. Correspondingly, the increased cell invasion and migration were also reversed by U0126 16. Moreover, elevated E-cadherin significantly suppressed the cell proliferation and migration and E-cadherin was inhibited by activating ERK/Snail signaling 17.…”
Section: Discussionmentioning
confidence: 90%
“…Because AKT and ERK are well-established activators of SNAI1 expression in cancer cells 15 , 16 , we tested whether they regulate the drastic elevation of SNAI1 levels in TN-resistant TNBC cells. To do so, we compared activated AKT and ERK levels in TN-resistant and parental cells using immunoblotting.…”
Section: Resultsmentioning
confidence: 99%